THE ROLE OF LEGAL SOCIOLOGY IN UNDERSTANDING CUSTOMARY LAW AND ISLAMIC SOCIETY - Ahmad Fadholi Hariri; Ahmad Sarwad; Bun Rafiq; Dani Wijaya Saputra; Masyuri Said Shahdan; M. Jibran Faiz; Andrey Nasrullah Kamal; Junaidi; Priya Pratama Surya Dewangga; Ahmad Faisal Mahendra (International Journal of Multidisciplinary Reseach, 2025)
This study explores the role of legal sociology in understanding the relevance and transformation of customary law (hukum adat) within modern society. Using a qualitative case study approach, this research investigates how traditional norms coexist, conflict, or integrate with state law in a community practicing strong adat values. The study reveals that legal sociology offers critical insights into the dynamic interaction between customary and formal legal systems, enabling a more contextual and culturally sensitive legal understanding.